1993
DOI: 10.1016/0014-5793(93)81688-v
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of diffusional hindrances, electrostatic repulsion and product inhibition on the kinetic properties of a bound acid phosphatase

Abstract: The kinetic properties of a soybean cell wall phosphatase were studied and compared under different environmental conditions. The native enzyme isolated from the wall exhibits classical Michaelis Menten kinetics. When buried into the cell wall, its natural environment, the enzyme mimics an apparent negative cooperativity. This deviation from hyperbolic dependence of the activity vs. the substrate concentration may result from an heterogeneous distribution of the enzyme molecules between the surface and the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Thiebart-Fassy and Hervagault [21] reported that more vigorous stirring would have led to a decrease in the unstirred layer thickness, that is, to a decrease in the contribution of diffusional hindrance (whenever dietary fibres are included). The end point of glucose diffusion equilibrium (glucose diffusion into the external solution) was found by measuring the external solution glucose content in dialysate at 0, 3, 6, 18 and 24 h time intervals.…”
Section: Glucose Movement In Vitromentioning
confidence: 99%
“…Thiebart-Fassy and Hervagault [21] reported that more vigorous stirring would have led to a decrease in the unstirred layer thickness, that is, to a decrease in the contribution of diffusional hindrance (whenever dietary fibres are included). The end point of glucose diffusion equilibrium (glucose diffusion into the external solution) was found by measuring the external solution glucose content in dialysate at 0, 3, 6, 18 and 24 h time intervals.…”
Section: Glucose Movement In Vitromentioning
confidence: 99%
“…Depression of GABA currents was also observed when phosphatase activity was inhibited either with a phosphate-based internal solution (Kennelly et al, 1993;Thiebart-Fassy and Hervagault, 1993;Weiner et al, 1993;Caselli et al, 1994;Gao and Fonda, 1994;Bernardi et al, 1995) or with 1 M microcystin-LR, an inhibitor of type 1 and 2A phosphatases (Honkanen et al, 1990). Data are summarized in Figure 6 A.…”
Section: A Component Of Cgmp-induced Depression Requires Pkgmentioning
confidence: 99%
“…B) and not submitted to electrostatic effects, the other one buried within the matrix (vPaqe, M) and therefore submitted to these effects [20,211. Therefore, the global enzyme activity as a function of Glc6P concentration can be expressed by the sum of two Michaelian terms related to the two populations, and mimicking a negative cooperativity, provided that the partition coefficient, I 7 is independent of the substrate concentration [20, 211. Under our experimental conditions, the overall reaction rate of the immobilized (and absorbed) phosphatase can be expressed as follows [22] : where with i = 1 or 2 (compartments 1 and 2) and subscriptj referring to the local metabolite concentration within the matrix . V,,,, and V,,,, are the maximal activities proportional to the enzyme molecule concentrations exposed at the surface of the membrane and buried in the membrane, respectively.…”
Section: Resultsmentioning
confidence: 99%